Myoid gonadal stromal tumor, a case report with review of the literature - Giuseppe D'Abbronzo; Andrea Ronchi; Maria Paola Belfiore; Elvira La Mantia; Florinda Feroce; Sandro Pignata; Sisto Perdonà; Renato Franco (Wolters Kluwer Medknow Publications, 2022)
The diagnosis of myoid gonadal stromal tumor (MSGT) can represent a difficult challenge, both for the extreme rarity of this neoplasm and for the clinical-radiological characteristics similar to other neoplasms of the testicle. The case management we present suggests how a complete differential diagnosis can be obtained by integrating ultrasonographic and pathological data.